Outcomes with chimeric antigen receptor t-cell therapy in relapsed or refractory acute myeloid leukemia: a systematic review and meta-analysis - Shahzad, Moazzam; Nguyen, Andrea; Hussain, Ali; Ammad-Ud-Din, Mohammad; Faisal, Muhammad Salman; Tariq, Ezza; Ali, Fatima; Butt, Atif; Anwar, Iqra; Chaudhary, Sibgha Gull; Lutfi, Forat; Ahmed, Nausheen; et al. (Frontiers in Immunology, 2023)
Background: We conducted a systematic review and meta-analysis to evaluate outcomes following chimeric antigen receptor T cell (CAR-T) therapy in relapsed/refractory acute myeloid leukemia (RR-AML). Methods: We performed a literature search on PubMed, Cochrane Library, and Clinicaltrials.gov. After screening 677 manuscripts, 13 studies were included. Data was extracted following PRISMA guidelines. Pooled analysis was done using the meta-package by Schwarzer et al. Proportions with 95% confidence intervals (CI) were computed. Results: We analyzed 57 patients from 10 clinical trials and 3 case reports. The pooled complete and overall response rates were 49.5% (95% CI 0.18-0.81, I2=65%) and 65.2% (95% CI 0.36-0.91, I2=57%). The pooled incidence of cytokine release syndrome, immune-effector cell associated neurotoxicity syndrome, and graft-versus-host disease was estimated as 54.4% (95% CI 0.17-0.90, I2=77%), 3.9% (95% CI 0.00-0.19, I2=22%), and 1.6% (95%CI 0.00-0.21, I2=33%), respectively. Conclusion: CAR-T therapy has demonstrated modest efficacy in RR-AML. Major challenges include heterogeneous disease biology, lack of a unique targetable antigen, and immune exhaustion.